Analysis of Syntax Error in The Preparation Book of Arabic Language Skills in The University - Nafisah, Firda Aiza (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This study aims to find the syntax errors in the Arabic text and correct (tashwib) existing errors to conform to the standard Arabic grammatical rules in the book Al-Haawi Fi Isti'dad Ikhtibar Kafaa'ah Al-Lughah Al-Arabiyyah. Through the text error analysis method, the standard of Arabic education book can be known. This Study uses a qualitative method with an applied linguistics approach in the field of syntax. The analysis technique of this study is the Al-Rajihi technique by identifying errors, clarifying errors, interpreting errors, and finally correcting errors. The results of the analysis showed that the researcher found as many as 13 syntax errors in the book Al-Haawi Fi Isti'dad Ikhtibar Kafaa'ah Al-Lughah Al-Arabiyyah which used in the preparation class for the Test of Arabic Foreign Language (TOAFL) by students of UIN Sunan Kalijaga Yogyakarta. These errors are classified into six types of errors, that are ism which pronounced as jar, the arrangement of ism (jumlah ismiyyah), the arrangement of fi’il (jumlah fi’liyayah), na’at man’ut, ism dhammir, and fi’il mudhari’. The errors are justified in accordance with the Arabic grammatical rules, namely Nahwu science.